توزيع الأدوار الأسرية بين الجنسين من منظور الوثائق الدولية - مصطفى, أ.م.د. عالية فرج (Sulaimani Journal for Humanities, 2023)
The research deals with the study and analysis of the materials contained in the three international documents: the Convention on the Elimination of All forms of Discrimination against Women, the Beijing Document and the Child Convention related to the division of family roles between the sexes, where the researcher focuses on distinguishing between gender roles and the stereotype roles of spouses In terms of the foundations adopted from the perspective of documents for the division of family roles between the sexes, the researcher adopts the descriptive approach and the content analysis approach to study the materials related to the distribution of family roles between the sexes within the family. Through the analysis of the materials and the items of the three documents, the researcher reached conclusions, including: The three documents confirm the need to consider the social dimension represented by gender as a basis for the division of family roles between the spouses, as well as the true sharing in the Family roles which translates gender equality into a degree of sameness between the sexes, which focuses on the equal division of all family roles between the sexes and ensuring the normalization of this through comprehensive strategies applied at the international, national and local levels through governments, the private sector, the media and international civil society organizations, including United Nations and local agencies.
Keywords: (Keyword) family roles; Gender roles; Gender perspective; international documents)